2019
DOI: 10.3390/app9235115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interlayer Cooling Time, Constraint and Tool Path Strategy on Deformation of Large Components Made by Laser Metal Deposition with Wire

Abstract: Laser metal deposition with wire (LMD-w) is a developing additive manufacturing (AM) technology that has a high deposition material rate and efficiency and is suitable for fabrication of large aerospace components. However, control of material properties, geometry, and residual stresses is needed before LMD-w technology can be widely adopted for the construction of critical structural components. In this study, we investigated the effect of interlayer cooling time, clamp constraints, and tool path strategy on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…However, the right-end of the build is lower than anticipated, because residual heat from the previous deposited layers causes the metal to flow more [116]. In general, proper deposition paths can notably reduce residual stresses and deformation, particularly in large scale WAAM fabrication [33,114]. in WAAM [113,114].…”
Section: Residual Stresses and Distortionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, the right-end of the build is lower than anticipated, because residual heat from the previous deposited layers causes the metal to flow more [116]. In general, proper deposition paths can notably reduce residual stresses and deformation, particularly in large scale WAAM fabrication [33,114]. in WAAM [113,114].…”
Section: Residual Stresses and Distortionmentioning
confidence: 98%
“…The repeated heating and cooling can cause thermal expansion and shrinkage of the deposited parts, leading to deformation, especially in large thin-walled components [109]. Residual stresses and distortion are closely related to deposition paths in WAAM [113,114]. Lee et al [114] reported that a bidirectional tool path with 180 • rotation decreased the residual stress by around 50% at the bottom corner of the sample, which potentially reduces the cracking susceptibility.…”
Section: Residual Stresses and Distortionmentioning
confidence: 99%
See 3 more Smart Citations